2013
DOI: 10.1063/1.4775404
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of GaAsP/InGaAs/GaAs strain-balanced multiple-quantum well solar cells

Abstract: A design of de GaAsP/InGaAs/GaAs solar cell is presented that allows to model high efficiency devices. The stress, tensile and compressive, are considered in order to compute the electron and hole dispersion relation E(k) in conduction and valence band. Similarly, the optical transitions in quantum well and barriers were evaluated to calculate the quantum internal efficiency and the photocurrent. GaAsP/InGaAs/GaAs solar cell is optimized to reach the maximum performance by means of J-V relation. Our model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In a previous paper, 3 it was shown that high SB-QWSC performance was achieved for 3% In composition. Moreover, for SB-QWSC with deeper quantum wells (higher indium fraction) the efficiency falls.…”
Section: Anisotropic Radiative Emission and Gainmentioning
confidence: 93%
See 4 more Smart Citations
“…In a previous paper, 3 it was shown that high SB-QWSC performance was achieved for 3% In composition. Moreover, for SB-QWSC with deeper quantum wells (higher indium fraction) the efficiency falls.…”
Section: Anisotropic Radiative Emission and Gainmentioning
confidence: 93%
“…Once the expressions for the effective density of states, the absorption coefficient, the radiative recombination current density, and photocurrent were found for SB-QWSC, then it is possibly to compute the J-V characteristic, and conversion efficiency (g) can be evaluated. 3,16 The dependence of conversion efficiency on back mirror reflectivity and quantum well number (N w ) is examined in Figure 6. This plot suggests that with the addition of a distributed Bragg reflector in the device, fewer quantum wells are required to grow in the i-region in order to achieve high performance.…”
Section: Influence Of Anisotropic Radiative Emission and Photon Rmentioning
confidence: 99%
See 3 more Smart Citations